Managers not MBAs : a hard look at the soft practice of managing and management development - Mintzberg, Henry (Berrett-Koehler Pub., 2005)
In his new book, Henry Mintzberg offers a sweeping critique of how managers are educated and how management, as a result, is practiced, and makes thoughtful - and controversial - recommendations for reforming both. Management, Mintzberg writes, is a practice that blends a great deal of craft (experience) with a certain amount of art (insight) and some science (analysis). Because conventional MBA programs are designed almost exclusively for young people with little if any managerial experience, and hence little art and no craft to draw upon, the programs overemphasize science, in the form of analysis and technique. Graduates leave with a distorted impression that management consists entirely of applying formulas to situations, which has had a corrupting, dehumanizing effect not just on the practice of management, but also on our organizations and our social institutions. Turning to how managers should be developed, Mintzberg describes in detail a set of innovative programs designed to address these shortcomings that he and a group of colleagues have put into practice: the International Masters in Practicing Management (IMPM). Finally, he outlines how business schools can transform themselves to become true schools of management. Managers Not MBAs presents the kind of bold, iconoclastic thinking readers have come to expect from the man Fast Company magazine called "one of the most original minds in management."